Design and Development of An Intelligent Automatic Tilapia Fish Farming Device in A Bucket Based on Internet of Things - Suni, Gina Amanah; Fadhli, Mohammad; Rose, Martinus Mujur (Indonesian Journal of Artificial Intelligence and Data Mining, 2025)
The cultivation of various freshwater fish species, such as catfish, tilapia, carp, and sepat, can be effectively managed through the budikdamber technique, where fish and vegetables are grown together in a single container. This research introduces an alternative method designed to control water temperature, automate fish feeding, and cover the container automatically when it rains. By integrating monitoring and control devices, budikdamber owners can manage automated feeding, monitor water temperature, measure pH levels, control water depth, and automatically activate rain covers. This smart device is expected to enhance budikdamber management efficiency, contributing to the improved welfare of the fish and overall system sustainability.